Vergleich zwischen der Schlierenmethode nach Toepler und der Hintergrundschlierenmethode zur Bestimmung akustischer Grössen eines Ultraschallwandlers - Olfert, Sergei; Henning, Bernd
Es gibt unterschiedliche Methoden, um räumliche Schallwechseldruckverteilungen in Flüssigkeiten zu erfassen. Viele dieser Verfahren haben zwei Nachteile. Sie sind zum einen invasiv, beeinflussen somit die sich ausbreitende Ultraschallwelle, und zum anderen sehr zeitaufwendig. Die Visualisierung von Ultraschallfeldern mittels Schlierenmethode ist eine schnelle und einfache Methode, um zweidimensionale Schallfelder nichtinvasiv zu analysieren. Ein besonderer Vorteil besteht darin, dass man unmittelbar resultierende Veränderungen im Schallfeld zum Beispiel bei Frequenzänderung, Sensorausrichtung… beobachten kann. In diesem Beitrag werden zwei dieser Verfahren vorgestellt. Die modifizierte Schlierenmethode nach Toepler, das im Weiteren als modifizierte Schlierenmethode bezeichnet wird, und die Hintergrund-schlierenmethode, das sich bisher hauptsächlich zur Strömungsvisualisierung etabliert hat [1]. Im ersten Teil werden beide Messverfahren erläutert, die realisierten Messaufbauten sowie Einsatzmöglichkeiten für die Schallfeldcharakterisierung kurz vorgestellt. Im zweiten Teil werden beide Verfahren verglichen und die Vor- und Nachteile bezüglich ausgewählter Messaufgaben bewertet.

Utilizing an Analytical Approximation for c44E to Enhance the Inverse Method for Material Parameter Identification of Piezoceramics - Rautenberg, Jens; Rupitsch, Stefan J.; Henning, Bernd; Lerch, Reinhard (7th International Workshop on Direct and Inverse Problems in Piezoelectricity)
There has been a lot of progress in finding measurable quantities of high in- formation content for the inverse determination of piezoelectric material properties. Since some material parameters (mainly \textgreek{e}S 11, e15and cE 44) do not or only marginally influence the electrical impedance over frequency, it is not sufficient to look only at the electri- cal impedance of discoidal piezoceramics [1]. Moreover, the parameter sensitivities vary with respect to the diameter--thickness ratio of the disc and the design of an ultrasonic transducer's piezoceramic has to match other requirements than those of a good material characterization [2, 3]. That is why it is still desirable to find model based approaches for parameter identification that either keep the technical effort low (e.g., only an impedance measurement) or increase speed of the inversion procedure. In this contribution we answer the question if an additional analytical approximation of cE 44, strictly following the ideas of Theocaris [4], in conjunction with a single measured elec- trical impedance will be sufficient for an accurate simulation of both, electrical impedance and surface normal velocity of a piezoceramic disc. Thereby, the remaining parameters are identified by means of the Inverse Method. Furthermore, we use the parameter ap- proximation as an initial guess and limiting boundary to speed up the inverse algorithm if both, electrical impedance and surface normal velocity are taken into account within the optimization procedure.

Luftultraschall-Abstandsmessung mit verkürztem Mindestabstand - Schröder, Andreas; Henning, Bernd
Bei der Luftultraschall-Abstandsmessung mit einem einzelnen Schallwandler ist der Mindestabstand durch die Sendesignaldauer und die Ausschwingzeit des Schallwandlers begrenzt. Daher führt die Verwendung von codierten Sendesignalen, wie sie z.B. für die Unterscheidung mehrerer Sender genutzt werden können, im Allgemeinen zu einer Vergrößerung des Mindestabstandes. Dieser Beitrag zeigt, dass der Mindestabstand bei codierten Sendesignalen durch eine geeignete Signalverarbeitung, bei der eine Trennung des Sende- und Empfangssignals erfolgt, deutlich verringert werden kann.

Model based separation of transmitted and received signal for single transducer distance measurement applications - Schröder, Andreas; Henning, Bernd
Simultaneous transmitting and receiving (STaR) enhances the utilization of single transducer ultrasound measurement systems. In distance measurement applications the dead zone can be reduced to nearly zero, independent of the transmitted signal. So it is possible to transmit codedsignals to identify different sensors without increasing the minimum distance. The electrical transducer signal consists of the electrical transmitted and received signal. A separation of these two signals can be done with a mathematical model of the electrical system. For this purpose it is necessary to digitize the electrical transducer signal. Due to the relative small amplitude of the received signal compared to the transmitted signal amplitude, a high resolution analog to digital converter (ADC) is needed. This leads to high requirements for the ADC. The necessary resolution limits the sample rate of the ADC. By down mixing the transducer signal using a coherent quadrature demodulation (CQD), as used in many high frequency ultrasound applications, the sample rate of the ADC can be reduced. In this contribution an airborne ultrasound distance measurement system with reduced dead zone is used to analyze the effects of this concept to the signal conditioning, system identification and system performance. The approach is compared with a system without CQD and an ADC with a lower resolution but a higher sample rate. By analyzing the pros and cons of both systems the usability of a CQD based system for a STaR application is evaluated. The distance measurement system used for the experiments is based on a 40 kHz airborne ultrasonic transducer. A gyrator based transmit amplifier delivers a system bandwidth of about 10 kHz. In the experiments, coded transmitted signals are used to measure the distance to a metal reflector. The main objectives are short distances between 0 mm and 200 mm. Here a separation of transmitted and received signal is necessary. The reflector distance is calculated by a cross correlation between transmitted and received signal.

Finite element simulation of single ultrasonic transducer with segmented electrodes to adjust the directional characteristic - Unverzagt, Carsten; Henning, Bernd
For many applications like level measurement and industry robotics it is of advantage if the directional characteristic of an ultrasonic transducer is changeable or adaptable for the improvement of spatial resolution. Often this goal is reached with the use of ultrasonic transducer arrays, which elements are driven with phase shifted excitation signals. One disadvantage of these solutions is the great effort for building such an array and the multi-channel sensor electronics. In this contribution the directional characteristic of a single air transducer with segmented electrodes is analyzed. Therefore a variable script based finite element model is used to discover the influence of different electrode configurations on the directional characteristic of a single piezoceramic transducer. Especially the influence on the angle of beam and the near field length are evaluated. The used variable model permits an optimization of the configuration with regards to the mentioned criteria. The findings will be used for the development of a level measurement system for bulk solids.
Keywords: Elektrode

Robuster Selbsttest mit Diagnose - Cook, Alejandro; Hellebrand, Sybille; Indlekofer, Thomas; Wunderlich, Hans-Joachim (5. GMM/GI/ITG Fachtagung "Zuverlässigkeit und Entwurf")

An exact algorithm for F-measure maximization - Dembczynski, K.; Waegeman, W.; Cheng, W.; Hüllermeier, Eyke (In Proceedings NIPS-2011, 25th Annual Conference on Neural Information Processing Systems, Granada, Spain)

Preference-based policy iteration: Leveraging preference learning for reinforcement learning - Cheng, W.; Fuernkranz, J.; Hüllermeier, Eyke; Park, S.H. (Proceedings ECML/PKDD-2011, European Conference on Machine Learning and Principles and Practice of Knowledge Discovery in Databases, Athens, Greece,)

Learning from label preferences - Fürnkranz, J.; Hüllermeier, Eyke (in Proceedings DS-2011, 14th International Conference on Discovery Science, number 6926 in LNAI)

Learning monotone nonlinear models using the Choquet integral - Fallah Tehrani, A.; Cheng, W.; Dembczynski, K.; Hüllermeier, Eyke (In Proceedings ECML/PKDD-2011, European Conference on Machine Learning and Principles and Practice of Knowledge Discovery in Databases, Athens, Greece,)

Preference-based CBR: First steps toward a methodological framework - Hüllermeier, Eyke; Schlegel, P. (In Proceedings ICCBR-2011, 19th International Conference on Case-Based Reasoning, number 6880 in LNAI)

Anwendungsszenarien als Werkzeug zur (V) Ermittlung des Nutzens von corporate social software - Trier, Matthias; Richter, Alexander; Mörl, Susanne; Koch, Michael (10th International Conference on Wirtschaftsinformatik)

CYBEREMOTIONS – Collective Emotions in Cyberspace - Ahn, Junghyun; Borowiec, Anna; Buckley, Kevan; Cai, Di; Chmiel, Anna; Czaplicka, Agnieszka; Dąbrowski, Grzegorz; Garas, Antonios; Garcia, David; Gobron, Stéphane; Hillmann, Robert; Hołyst, Janusz; et al. (Procedia Computer Science)

Dynamische Analyse von Netzwerken elektronischer Kommunikation. Kann der Zentralität getraut werden? - Trier, Matthias; Bobrik, Annette (Netzwerkanalyse und Netzwerktheorie)

Anwendungsszenarien als Werkzeug zur (V)Ermittlung des Nutzens von Corporate Social Software - Richter, Alexander; Mörl, Susanne; Trier, Matthias; Koch, Michael

Bipartite ranking through minimization of univariate loss - Kotlowski, W.; Dembczynski, K.; Hüllermeier, Eyke (in Proceedings ICML-2011, 28th International Conference on Machine Learning, Washington, USA)

Memory Virtualization for Multithreaded Reconfigurable Hardware - Agne, Andreas; Platzner, Marco; Lübbers, Enno (Proceedings of the International Conference on Field Programmable Logic and Applications (FPL))

Design and architectures for dependable embedded systems - Henkel, Jörg; Hedrich, Lars; Herkersdorf, Andreas; Kapitza, Rüdiger; Lohmann, Daniel; Marwedel, Peter; Platzner, Marco; Rosenstiel, Wolfgang; Schlichtmann, Ulf; Spinczyk, Olaf; Tahoori, Mehdi; Bauer, Lars; et al. (Proceedings of the seventh IEEE/ACM/IFIP International Conference on Hardware/software Codesign and system synthesis - CODES+ISSS '11)

Complex Queries in P2P Networks with Resource-Constrained Devices - Dannewitz, Christian; Biermann, Thorsten; Dräxler, Martin; Karl, Holger (Journal of Advances in Information Technology)

Modellbasierte Konzipierung eines hybriden Energiespeichersystems für ein autonomes Schienenfahrzeug - Gausemeier, Jürgen; Dumitrescu, Roman; Tschirner, Christian; Stille, Karl Stephan Christian (Tag des Systems Engineering)
Die Kommunikations- und Informationstechnik eröffnet neue Möglichkeiten zur Erweiterung und Optimierung der Systemfunktionalität mechatronischer Systeme. Die erfolgreiche Entwicklung dieser fortgeschrittenen mechatronischen Systeme bedarf sowohl einer besonderen Strukturierung der Informationsverarbeitung als auch einer geeigneten modellbasierten Entwurfstechnik. SysML und CONSENS eignen sich für den Entwurf derartiger Systeme. Die Anwendung von CONSENS wird anhand eines Demonstrators vertieft.
Keywords: Produktentstehung; HES; Hybrider Energiespeicher; CONSENS; SysML; SFB614; LEA-Publikation; Eigene